Dampak Pelatian Membangun Skill dan Kreatifitas Desain Grafis pada Pelaku Usaha Mikro, Kecil dan Menengah di Era Digital 4.0 - Ginting, Guidio Leonarde; Silalahi, Natalia (Journal of Social Responsibility Projects by Higher Education Forum, 2025)
Punden Rejo Village, located in Tanjung Morawa District, Deli Serdang Regency, possesses significant economic potential for the development of Micro, Small, and Medium Enterprises (MSMEs) due to its strategic location along North Sumatra's main transportation routes. However, the majority of MSME operators in this village face constraints in adapting to digital technology, particularly in marketing and product branding, which have become vital necessities in the digital 4.0 era. One of the primary challenges is the limited graphic design skills, an essential element for attracting consumer interest through professional product packaging and promotional materials. This community service initiative aims to enhance the graphic design capabilities of MSME operators in Punden Rejo Village through training using Adobe Express application. The activity involved 30 local MSME operators as partners. The implementation methods included situation analysis through interviews and observations, development of training modules, and practical workshops conducted at the Punden Rejo Village Hall. The training program covered basic graphic design introduction, hands-on practice in creating product packaging designs, digital banners, and promotional posters using Adobe Express. The training results demonstrated a significant improvement in participants' understanding and graphic design skills, reflected in their ability to produce attractive and targeted designs. Challenges related to device limitations and internet connectivity were addressed through an intensive mentoring approach. The use of Adobe Express proved effective as a graphic design solution for beginners, supporting the creativity of MSME operators in producing competitive designs for the digital market. This training is expected to encourage the sustainable digital transformation of MSMEs in Punden Rejo Village.